Deployment-Related Respiratory Disease: Where Are We? - Krefft, Silpa D.; Zell-Baran, Lauren M. (Seminars in Respiratory and Critical Care Medicine, 2023)
Military personnel and veterans who have deployed to Afghanistan, Iraq, and parts of Southwest Asia (SWA) since 1990 are at risk of developing a host of respiratory symptoms and deployment-related respiratory diseases (DRRDs). This review aims to summarize our current understanding of DRRD and inform pulmonary practitioners of recent updates to DRRD screening, diagnosis, evaluation, and management. The most common respiratory diseases in these patients include asthma, chronic sinonasal disease, laryngeal disease/dysfunction, and distal lung disease. Pulmonary function testing and chest imaging are the most commonly used diagnostic tools, but techniques such as lung clearance index testing via multiple breath washout, forced oscillation testing/impulse oscillometry, and quantitative chest computed tomography (CT) assessment appear promising as noninvasive modalities to aid in lung disease detection in this population. We also summarize guidance on conducting an occupational and deployment exposure history as well as recommendations for testing. Finally, we discuss the Sergeant First Class Heath Robinson Honoring our Promise to Address Comprehensive Toxics Act of 2022 (PACT Act) that includes a list of health conditions that are “presumptively” considered to be related to SWA military deployment toxic exposures, and provide resources for clinicians who evaluate and treat patients with DRRD.
Keywords: deployment-related respiratory disease; veterans; bronchiolitis; asthma; burn pits; PACT Act